Workshop Model Pembelajaran Berbasis Online sebagai Alternatif Pembelajaran Ekonomi di Era Covid-19 - Heni Purwa Pamungkas; Ni’matush Sholikhah; Jun Surjanti; Norida Canda Sakti (Jurnal Pengabdian Pada Masyarakat, 2021)
WORKSHOP MODEL BASED ONLINE LEARNING AS AN ALTERNATIVE OF ECONOMICS LEARNING IN COVID-19 ERA. The Covid-19 pandemic spread rapidly since March 2020; it impacts in a change in the learning mode from face-to-face learning to online learning. It led various problems felt by teachers and students. Online learning that has been carried out is dominated by assignments and minimal interaction between teachers and students. One of the factors causing the ineffectiveness of online learning is that teachers are not accustomed to arranging online learning. The purpose of this service community activity is to provide training for Economics teachers in developing online learning models as an alternative of Economics learning. The subject of this service community activity are Economics teachers in East Java. These activities are divided into two stages, namely (1) seminars, where participants get material related to the essence of online learning; and (2) assistance in developing online learning models. The results of this service community activity concluded that most of the participants gave a positive response to the training that had been implemented and they were able to arrange online classes well.